Assistive Technology and Educational Outcomes among Students with Visual Impairment: A Review of Emerging Trends - Mr. Hasan Deen Khan; Dheeraj Kumar Nagar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Assistive technology has transformed the educational landscape for students with visual impairment, expanding access to print, mathematics, graphics, and independent navigation in ways that were unimaginable a generation ago. This paper reviews the trajectory of assistive technology development for learners who are blind or have low vision, tracing the shift from analog tools such as slates, styluses, and braillewriters to contemporary digital ecosystems built around screen readers, refreshable Braille displays, optical character recognition, and artificial-intelligence-driven image description. It examines the empirical evidence linking assistive technology use to educational outcomes, including literacy development, mathematics achievement, and independent participation in mainstream classrooms, while also addressing persistent barriers such as cost, training gaps, device abandonment, and inequitable access across regions and socioeconomic groups. The paper further considers emerging trends, including AI-based scene description, tactile graphics generation, and multimodal learning tools, and discusses their implications for future practice. It concludes that technology alone does not guarantee improved outcomes; rather, outcomes depend on the integration of technology within a broader instructional framework that includes explicit skills training, ongoing technical support, and collaboration between teachers of students with visual impairment and general educators.